Because - Willems, Mo; Ren, Amber (New York : Hyperion Books For Children, 2019)
A series of events, some seemingly very insignificant, lead to a young girl attending a life-changing concert.
K-3
3.4
AD820L
Keywords: Musicians -- Fiction; Concerts -- Fiction; Serendipity -- Fiction; Musicians -- Juvenile fiction; Concerts -- Juvenile fiction